Management of a Disassembly Line using Two Types of Kanbans - Kenichi Nakasima; Mitsutoshi Kojima; Surendra M. Gupta (International Journal of Supply Chain Management, 2012)
The continuous growth in consumer waste has seriously threatened the environment. For this reason, environment conscious manufacturing has emerged to be an important attribute that has been embraced by companies to support the environmental laws, social responsibilities as well as profitability resulting in increased awareness of product recovery. One of the first operations in product recovery is disassembly which involves the separation of the desired components, subassemblies, and materials from end-of-life or returned products. A disassembly line is perhaps the most suitable setting for disassembly of products in large quantities. In this paper, a multi-kanban mechanism using two types of kanbans, viz., a component kanban and a subassembly kanban, is used to control the disassembly line. We consider an example from the automobile industry to illustrate the methodology and investigate the fluctuations in components and subassemblies inventories, average waiting times and backorder rates using simulation. The results demonstrate the effectiveness of utilizing the multi-kanban mechanism in a disassembly line.